Metallocomplex catalysis in oxidation processes. Kinetics and mechanisms. - L. I. Matienko; L. A. Mosolova; G. E. Zaikov (Тонкие химические технологии, 2009)
Ways of increasing catalytic activity of complexes of transition metals towards oxidation of alkylarenes with molecular oxygen, described in the literature within last 10-15 years, are reviewed. Attention is focused on the original method of controlling the catalytic activity of complexes of M(acac)n (M=Ni(II), Fe(II,III), Co(II)) in the oxidation reactions of alkylarene (e.g., ethylbenzene and cumol) to hydroperoxides by introducing the mono- or polydentate electron-donating ligands L2. Modeling of the catalytically active complexes of nickel as selective catalysts for ethylbenzene oxidation to α-phenylethylhydroperoxide by introducing phenol (PhOH) in the binary system {Ni(II)(acac)2+L2}, and also active complexes of nickel or iron by using quaternary ammonium salts and macrocyclic polyethers as L2, is successfully realized by the authors. The role of H-bonding in the mechanisms of the homogeneous catalysis is discussed. A strategy of controlling the catalytic activity of Fe(II,III)(acac)nL2 complexes (L2 =R4NBr or 18-crown-6 (18C6) by introducing small amounts of H2O (~10-3 mol/l) is proposed. The activity of Ni and Fe catalysts in the processes of radical chain initiation (O2 activation) and radical chain propagation (Catalyst + RO2 →) in the reactions of ethylbenzene oxidation is discussed. The bibliography includes 144 references.